2006
DOI: 10.1080/00343400600757734
|View full text |Cite
|
Sign up to set email alerts
|

Retail planning and institutional property investment

Abstract: Jackson C. (2006) Retail planning and institutional property investment, Regional Studies 40, 555-561. Investment in town centre retail property markets is dominated by institutions. Thus, sustaining and enhancing the vitality and viability of town centres, which is a key role of local planning authorities, is crucial to maintain the attractiveness of the area to investors. Investor movements into and out of markets can have a significant impact on the market and wider local and regional economic success. Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…TCM is aimed at coordinating a more effective use of existing public resources, providing a lever to secure private-sector investment, providing a new policy and resource priority and providing a vehicle for community participation and mobilization (Donaldsons and Healey and Baker, 1994). Donaldsons and Healey and Baker (1994) found that initially there was often limited financial support and involvement for TCM from the private sector, while Jackson (2006) suggests that the guidance has been subject to varied interpretation in different areas. Business Improvement Districts (BIDs) share similar characteristics to TCM schemes in that both are based on partnership and have the aim of providing the conditions to increase visitor numbers and encourage inward investment (Cook, 2009).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM is aimed at coordinating a more effective use of existing public resources, providing a lever to secure private-sector investment, providing a new policy and resource priority and providing a vehicle for community participation and mobilization (Donaldsons and Healey and Baker, 1994). Donaldsons and Healey and Baker (1994) found that initially there was often limited financial support and involvement for TCM from the private sector, while Jackson (2006) suggests that the guidance has been subject to varied interpretation in different areas. Business Improvement Districts (BIDs) share similar characteristics to TCM schemes in that both are based on partnership and have the aim of providing the conditions to increase visitor numbers and encourage inward investment (Cook, 2009).…”
Section: Interventionmentioning
confidence: 99%
“…It may be that some of these schemes have been responsible for averting the decline of retail areas (Grail, 2001;ODPM, 2003ODPM, , 2004 and Jackson andWatkins (2005, 2007) found that, in part, they positively affected investors' market perceptions and, therefore, investor demand. The response, attitude and actions of a local planning authority are also seen as key to the viability of a retail location (Jackson & Watkins, 2011).…”
Section: Interventionmentioning
confidence: 99%
“…These retailers, often placed as anchors in large shopping malls, seek to internalize the benefits of comparison shopping and at the same time are the most likely to strive for distinctive market areas (Stahl 1987). Phoenix offers an opportunity to understand retail location in cities beyond current geographical emphasis on regulation, planning, and store formats (Hernandez and Simmons 2006;Jackson 2006;Coe and Wrigley 2007). Although municipal governments strongly encourage development in certain sectors and formats, especially auto-malls, big-box-focused nodes, and regional shopping centers, zoning alone cannot explain widespread preferences to cluster near competitors or stores in other sectors.…”
Section: Discussionmentioning
confidence: 99%
“…These routes are dotted with shops selling an astounding range of goods that fuel an appetite for gasoline, which seems to be sold at every major intersection. Recent geographical analyses of retailing have stressed the roles of regulation and planning in store development strategies ( Jackson 2006;Guy and Bennison 2007), specific retailers' store formats and spatial strategies and associated costs of site acquisition (González-Benito 2005;Coe and Wrigley 2007), the importance of cross-or multipurpose shopping in explaining store clustering (Oppewal and Holyoake 2004;Teller 2008), the geography of chain-store national expansion (Graff 2006;Zook and Graham 2006), and the influence of consumer culture on retail districts and shopping behavior (Warf and Chapman 2006). These approaches mostly rely on case studies of retailers or single sectors to describe spatial patterns and place characteristics.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Adams and Watkins (2014) argue that these models tend to under-elaborate the multi-dimensional and complex nature of policy interventions and of state influence on markets. There are three important problems: (i) they under-state the importance of policy in creating a setting for investment and thus fail to allow for the impact on the demand-side of the market (Begg, 2002;Jackson, 2006;Jackson & Watkins, 2011); (ii) they tend to overlook the complex and often conflicting inter-play between different policy initiatives (Wong & Watkins, 2009); and (iii) they fail to take account of the importance of institutional design in mediating and mitigating the intended impacts of policy interventions (Adams & Tiesdell, 2010). Adams and Watkins (2014) go on to argue that a more pluralist research approach is required if we are to fully understand the relationship between the state (policy instruments and strategies) and market outcomes, including the level of development activity.…”
Section: Literature Reviewmentioning
confidence: 99%